Reconstruction of Accounting Education Purpose Concept through the Thoughts of Ki Hadjar Dewantara - Yohan Bakhtiar; Dion Yanuarmawan; Iwan Triyuwono; Gugus Irianto (International Journal of Religious and Cultural Studies, 2019)
This study aims at exploring the fact in accounting education at college and formulating the concept of accounting education based on the thoughts of Ki Hadjar Dewantara, enveloped in his two books: education and culture. Ki Hadjar Dewantara’s critical-spiritualist-nationalist paradigm is used as a perspective to analyse the present accounting education. This study uses a qualitative approach and case studies as a research strategy. The substance (indicator) of spirituality value (Tauhid ontology and orderliness in physical and spiritual), moral value (the balance of Cipta-Rasa-Karsaor Tri-Sakti), enhanced degree of humanity, and independence values (freedom, independent and partiality to Indonesian people) were the method in this study. The result of this study shows that accounting education reality at economics faculty, Real Learning University does not reflect the values of Ki Hadjar Dewantara’s idealistic thinking. A formulation of accounting education purpose concept in universities must be established to produce a perfect human with pure spirituality through spiritual, moral and independence value. This concept also can be interpreted as a struggle to bring love in accounting education purpose concept.